(untitled) (Sciences & Technologie. C, Biotechnologies, 2013)
The work presented concerns the study of the enrichment of the bread with the wheat germ. We enriched the bread with the germ once in a state not crushed and another in a state crushed with the following proportions: 2.5 - 5 - 7.5 - 10 - 12.5 and 15 % . We characterized our samples by carrying out chemical analyses, also we determined the content of gluten also its rheological properties in particular the softening and the extensibility and the realization of a bread making test.With the end we carried out the discussion of the results obtained of which most significant: The incorporation of the germ is acceptable with proportions going up to 5%. The use of the germ in a crushed state is advised in order to avoid the presence of the tasks on the crust of the bread what can obstruct the consumer.